2009
DOI: 10.1002/gps.2274
|View full text |Cite
|
Sign up to set email alerts
|

At‐risk alcohol drinking in primary care patients aged 75 years and older

Abstract: Multivariate analysis revealed that, apart from liver disease, at-risk drinking in a non-demented population aged 75 and over was associated with relatively good physical and mental health. Nevertheless, public prevention measures should focus on at-risk drinkers to make them aware of potential risks of high alcohol consumption in old age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 16 publications
3
30
1
2
Order By: Relevance
“…The alcohol consumption rates in our study are in line (consumers 62.2%) with the statistics of Finnish National Public Health Institute, where 65.2% of Finnish elderly aged 65–84 years had consumed alcohol in the precedent year (54% of females and 77% of males) in 2007 (Laitalainen et al ., 2008). The proportion of at‐risk users is fairly well in line with previous studies (Hirata et al ., 2009; St John et al ., 2008; Weyerer et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alcohol consumption rates in our study are in line (consumers 62.2%) with the statistics of Finnish National Public Health Institute, where 65.2% of Finnish elderly aged 65–84 years had consumed alcohol in the precedent year (54% of females and 77% of males) in 2007 (Laitalainen et al ., 2008). The proportion of at‐risk users is fairly well in line with previous studies (Hirata et al ., 2009; St John et al ., 2008; Weyerer et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The older population and its different cohorts are not homogeneous but culturally and socially diverse. Alcohol consumption is a complex phenomenon related to cohort life styles, gender, course of life, history of alcohol consumption, social patterns, physiology, cultural heritage, health condition, drinking norms, and moral principles (Klipstein‐Grobusch et al ., 2002; Sieri et al ., 2002; Tigerstedt and Törrönen, 2005; Bjørk et al ., 2008; Haarni and Hautamäki, 2008; Trevisan, 2008; Weyerer et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For predementia syndromes, in a group of 369 nondemented, community‐dwelling older men who participated in the National Heart, Lung, and Blood Institute Twin Study, alcohol consumption was found to be slightly protective (RR: 0.93; 95% CI: 0.88–0.99); but if individuals with CVD were excluded from the analysis, this association disappeared (DeCarli et al ., ). Very recently, in the cross‐sectional section of the Mayo Clinic Study of Aging, moderate alcohol consumption was associated with a decreased odds ratio (OR) of MCI and aMCI (but not naMCI; Roberts et al ., ), whereas in the German AgeCoDe Study, there was no cross‐sectional evidence of association between alcohol consumption and MCI and its subtypes (Weyerer et al ., ; Table ). The impact of alcohol consumption on the incidence of MCI was evaluated in 1445 cognitively normal individuals and on its progression to dementia in 121 patients with MCI, aged 65 to 84 years, participating in the Italian Longitudinal Study on Aging.…”
Section: Alcohol Consumption MCI and Dementiamentioning
confidence: 97%
“…Drinking behaviour. Marital status and cohabitation have been positively associated with alcohol misuse among older adults [31][32][33]. A recent systematic review found a strong link between social engagement and alcohol use among older adults [34].…”
Section: Model Rulesmentioning
confidence: 99%